Technology of nitrogen oxide extracting out of the furnace gases with application of mechanical activation - Кудрявцев, Сергій Олександрович (Eastern-European Journal of Enterprise Technologies, 2012)
The combined method is considered the most promising, after the analysis of existing methods of furnace gases cleaning of coal power units from nitrogen oxides. It is suggested to implement the process of adsorption in vybroliquefied layer of mechanically activated sorbent and its recycling to the stage of desorption, and after desorption to direct the concentrated stream of toxicants on the stage of absorption or destruction. Adsorber of vybroliquefied layer allows you to adjust the intensity of the mechanical activation of the adsorbent surface directly into the absorber at operating conditions. This method will provide uniform access of the active surface of the sorbent. This increases the efficiency of sorption capacitance of the sorbent. This method can provide a high degree of purification of furnace gases from NOx and improvement of techno-economic performance in comparison with existing industrial technologies of toxicants neutralization. Application of mechanical activation enhances the removal of nitrogen oxides by 10-15% and increases the adsorption capacity of ash to 2.5 times, as well as makes it possible to adsorb under high concentration of ash in the furnace gases. Such concentration will not prevent the adsorption but, driven by mechanical activation to an active state, can actively absorb nitrogen oxides.